Air Quality in India: A Review Paper (International Journal of Innovative Research in Computer Science & Technology, 2020)
Delhi, India's state capital, has a reputation for  being one of the world's most densely populated cities. As a  consequence of their findings in 2014, the World Health  Organization (WHO) released this. 2014, Bandyopadhyay et  al., Bandyopadhyay et al., Bandyopadhya It is  unquestionably a concern for India's future generations. We  are aware of the detrimental impacts of environmental  pollutants and poisons on human and other living things'  health as well as the ecosystem. Children and the elderly are  the people who are most vulnerable to the pollutants'  negative effects. To prevent environment pollution in India's  major cities, a number of critical initiatives should be taken,  as well as certain strict restrictions. In India, deadly diseases  such as cancer are on the rise. Pollution is undoubtedly to  blame for the rise in disease rates. Air pollution occurs when  vapours, tiny particles, smoke, or odors are emitted into the  air in a manner that is harmful to people, animals, and plants.  Air pollution endangers the well-being of the individuals as  well as all other living creatures on our globe.
Keywords: Air; India; Pollution,; Quality